The leverage of hedge funds and the risk of their prime brokers - Karagiorgis, Ariston; Anastasiou, Dimitrios; Drakos, Konstantinos; Ongena, Steven (Journal of Financial Stability, 2026)
Using an extensive matched hedge fund-prime broker panel dataset for the period 2001–2021, we document a strong positive relationship between hedge fund leverage and prime broker’s stock price crash risk after controlling for other crash risk drivers. Our results are not only statistically, but also economically significant, showing that a one-standard-deviation increase in hedge fund leverage is associated on average with an increase of around 5% of a standard deviation in the negative skewness or the down-to-up-volatility of bank stock returns. Moreover, they remain robust when accounting for endogeneity and conducting many robustness checks. We also document that some investment strategies, such as one focusing on fixed income, appear to decrease the slope of the risk metrics of prime brokers, and ultimately leading to lower stock price crash risk.